The Effect of Compensation and Work Environment Towards Budget Manager Performance with Organization Commitment as A Variable of Mediation - Windi Wulandari; Vince Rahmawati; Taufeni Taufik (Universitas Riau, 2020)
This objective of this studyis to investigate the effect of compensation and work environment on budget managers’ performance. Furthermore, this study also want to investigate the mediating role of organizational commitmen. The population in this study were all OPDs in the Riau Province region in the Indragiri Hilir Regency. The sampling method used in this study was purposive sampling, so as many as 58 OPD (Regional Apparatus Organizations) were obtained as samples. This study uses primary data by distributing questionnaires to heads of regional government organizations, financial administration officials, officials of technical implementation activities, and treasurers of expenditure in each OPD. The statistical method used to test the hypothesis is the Structural Equation Model (SEM) based on Partial Least Square (PLS) with the WarpPLS 6.0 program. The results shows that compensation and work environment directly affect budget managers’ performance.This study also found that organizational commitment mediates the effect of compensation and work environment on budget managers’ performanceThis objective of this studyis to investigate the effect of compensation and work environment onbudget managers’ performance. Furthermore, this study also want to investigate the mediating role of organizational commitmen.The population in this study were all OPDs in the Riau Province region in the Indragiri Hilir Regency. The sampling method used in this study was purposive sampling, so as many as 58 OPD (Regional Apparatus Organizations) were obtained as samples. This study uses primary data by distributing questionnaires to heads of regional government organizations, financial administration officials, officials of technical implementation activities, and treasurers of expenditure in each OPD. The statistical method used to test the hypothesis is the Structural Equation Model (SEM) based on Partial Least Square (PLS) with the WarpPLS 6.0 program. The results shows that compensation and work environment directly affect budget managers’ performance.This study also found that organizational commitment mediates the effect of compensation and work environment on budget managers’ performance